2022
DOI: 10.1021/jacs.1c13397
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies Yield Improved Protocols for Base-Catalyzed Anti-Markovnikov Alcohol Addition Reactions

Abstract: The catalytic anti-Markovnikov addition of alcohols to simple alkenes is a longstanding synthetic challenge. We recently disclosed the use of organic superbase catalysis for the nucleophilic addition of alcohols to activated styrene derivatives. This article describes mechanistic studies on this reversible reaction, including thermodynamic and kinetic profiling as well as computational modeling. Our findings show the negative entropy of addition is counterbalanced by an enthalpy that is most favored in nonpola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…To this end, we were inspired by a separate area of work in our laboratory focused on improving base-catalyzed alcohol addition reactions to alkenes . As part of those efforts, we recently reported thermodynamic and kinetic studies on the reversible addition of oxygen pronucleophiles to styrene derivatives . The K eq values for these reactions indicate that phenol pronucleophiles, compared to water, drastically favor the elimination products (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we were inspired by a separate area of work in our laboratory focused on improving base-catalyzed alcohol addition reactions to alkenes . As part of those efforts, we recently reported thermodynamic and kinetic studies on the reversible addition of oxygen pronucleophiles to styrene derivatives . The K eq values for these reactions indicate that phenol pronucleophiles, compared to water, drastically favor the elimination products (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with our previous studies that revealed alcohol addition to styrenes is both kinetically and thermodynamically challenging, indicating a more nucleophilic water surrogate is necessary for addition. 15,19 However, alcohols comprised of common aliphatic protecting groups, such as tert -butanol and 2-trimethylsilylethanol, provide low addition yields. Examination of cyclopropyl-substituted alcohols led to the discovery that 1-cyclopropylethanol undergoes addition in 82% isolated yield.…”
Section: Resultsmentioning
confidence: 99%
“…We recently disclosed the use of the phosphazene superbase P 4 - t -Bu or 18-crown-6-ligated KO- t -Bu as basic catalysts for the nucleophilic addition of alcohols to aryl-substituted alkenes. 15,16 Water does not participate in this reaction, so we instead sought a nucleophilic “protected water” source that could be used to achieve formal hydration (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphazenes have strong basicity and effectively generate anion species by deprotonation of alcohols, pyrroles, and the αC–H of ketones and esters . The anionic species produced by deprotonation with phosphazene bases have been termed “naked anions” because of the noncoordinating phosphazene counterion and have high nucleophilicity . We envisaged that this property of phosphazene bases could be leveraged with amides to provide a useful method for hydroamidation.…”
mentioning
confidence: 99%